A putative truncated cytokine receptor gene transduced by the myeloproliferative leukemia virus immortalizes hematopoietic progenitors - Souyri, Michèle; Vigon, Isabelle; Penciolelli, Jean-François; Heard, Jean-Michel; Tambourin, Pierre; Wendling, Françoise (Cell, 1990)
The myeloproliferative leukemia virus (MPLV) is an acute leukemogenic murine replication-defective retrovirus. By sequencing the envelope gene of a biologically active MPLV clone, we found that this region comprises a novel oncogene named v- mpl in phase with two parts of the Friend murine leukemia virus envelope gene. The MPLV env region could encode an env-mpl fusion polypeptide that presents the characteristics of a transmembrane protein. We show that in vitro infection of bone marrow cells with helper-free MPLV readily yields immortalized factor-independent hematopoietic cell lines of different lineages. In mice, the c- mpl proto-oncogene is expressed in hematopoietic tissues as a 3 kb mRNA. Since v- mpl shares strong structural analogies with the hematopoietin receptor superfamily, it is likely that MPLV has transduced a truncated form of an as yet unidentified hematopoietic growth factor receptor.